G-protein-coupled receptor allosterism: the promise and the problem(s). (26th October 2004) - Christopoulos, A.; May, L.T.; Avlani, V.A.; Sexton, P.M.
Abstract : Allosteric modulators of G-protein-coupled receptors interact with binding sites that are topographically distinct from the orthosteric site recognized by the receptor's endogenous agonist. Allosteric ligands offer a number of advantages over orthosteric drugs, including the potential for greater receptor subtype selectivity and a more 'physiological' regulation of receptor activity. However, the manifestations of allosterism at G-protein-coupled receptors are quite varied, and significant challenges remain for the optimization of screening methods to ensure the routine detection and validation of allosteric ligands.